2007
DOI: 10.1002/hep.21476
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone preconditioning: Protection against ischemia-reperfusion liver injury in the rat

Abstract: Recently, we reported that oxidative stress due to 3,3,5-triiodothyronine (T 3 )-induced calorigenesis up-regulates the hepatic expression of mediators promoting cell protection. In this study, T 3 administration in rats (single dose of 0.1 mg/kg intraperitoneally) induced significant depletion of reduced liver glutathione (GSH), with higher protein oxidation, O 2 consumption, and Kupffer cell function (carbon phagocytosis and carbon-induced O 2 uptake). These changes occurred within a period of 36 hours of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 41 publications
6
87
0
3
Order By: Relevance
“…The hormetic responses involved in thyroid hormone-induced liver preconditioning against IR injury (78) are also observed in the heart (88,89), with a pattern of protection closely resembling that of ischemic preconditioning (90), and constitute a preconditioning strategy that have clinical potential. This is an important issue considering that pharmacological and other liver preconditioning maneuvers have not been transferred to clinical application, with the exception of ischemic preconditioning (91).…”
Section: Discussionmentioning
confidence: 99%
“…The hormetic responses involved in thyroid hormone-induced liver preconditioning against IR injury (78) are also observed in the heart (88,89), with a pattern of protection closely resembling that of ischemic preconditioning (90), and constitute a preconditioning strategy that have clinical potential. This is an important issue considering that pharmacological and other liver preconditioning maneuvers have not been transferred to clinical application, with the exception of ischemic preconditioning (91).…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately increases liver iNOS expression and activity 232:2 together with other markers of oxidative stress including decreased liver glutathione content (an important antioxidant) and higher protein oxidation (Fig. 2B) (Tapia et al 1997, 2006, Valencia et al 2004, Fernandez et al 2005, 2007a. Conversely, another study found that T 3 inhibited STAT3 signalling in macrophages after LPS or IL-6 stimulation and had no effect on TNFα induction and NFκB activation in vitro (Contreras-Jurado et al 2016).…”
Section: Thyroid Hormone Metabolism In Tissue-resident Macrophagesmentioning
confidence: 96%
“…Several studies by the same group have analysed the effect of TH administration on rat liver and the role of Kupffer cells in this process. T 3 administration induces oxidative stress in the liver (Tapia et al 1997, 2006, 2010, Valencia et al 2004, Fernandez et al 2005, 2007a,b, 2008. This is thought to be mediated via Kupffer cells, which demonstrate hyperplasia, increased phagocytic capacity, increased ROS generation and tumour necrosis factor α (TNFα) production in response to T 3 administration in vivo (Fig.…”
Section: Thyroid Hormone Metabolism In Tissue-resident Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prolonged stress may cause an elevation in cortisol concentrations as the adrenal glands respond to the stress. The high cortisol levels inhibit the conversion of T4 to T3 [41]. On the other hand, loss of thyroid-binding protein in urine under the effects of oxidative stress could be another cause of decrease in serum T3 and T4 levels.…”
Section: Discussionmentioning
confidence: 99%